MODEL PENDIDIKAN LITERASI KEUANGAN SYARIAH BAGI KELUARGA DAN GENERASI MUDA MUSLIM - Lasawedy, Aslamuddin (Penerbit Widina, Widina Media Utama, 2025)
The model of sharia financial literacy education plays a crucial role in fostering healthy, sustainable financial awareness rooted in Islamic values. This study aims to formulate a relevant model of sharia financial planning literacy education for Muslim families, school students, and university learners through a literature review. The research method applied is library research by analyzing academic articles, books, and scientific publications published between 2019 and 2024. The findings reveal that sharia financial literacy encompasses not only technical skills such as cash flow management, debt control, emergency funds, takaful, halal investment, and wealth distribution through zakat, hibah, waqf, and inheritance, but also character building and the internalization of Islamic values in financial decision-making. This educational model is expected to enhance literacy, awareness, and competence among Muslim families and the younger generation in managing finances according to sharia principles, thereby achieving financial well-being aligned with spiritual and social sustainability. Thus, sharia financial literacy can serve as a strategic instrument to strengthen the economic resilience of the Muslim community while reinforcing Islamic values in daily life.ABSTRAKModel pendidikan literasi keuangan syariah memiliki peran penting dalam membangun kesadaran finansial yang sehat, berkelanjutan, dan berlandaskan nilai-nilai Islam. Penelitian ini bertujuan merumuskan model pendidikan literasi perencanaan keuangan syariah yang relevan bagi keluarga Muslim, siswa, dan mahasiswa melalui kajian literatur. Metode penelitian menggunakan library research dengan penelusuran artikel akademik, buku, dan publikasi ilmiah pada periode 2019–2024. Hasil kajian menunjukkan bahwa literasi keuangan syariah tidak hanya mencakup keterampilan teknis, seperti pengelolaan arus kas, pengendalian utang, dana darurat, takaful, investasi halal, serta distribusi kekayaan melalui zakat, hibah, wakaf, dan warisan, tetapi juga pembentukan karakter dan internalisasi nilai Islami dalam pengambilan keputusan finansial. Model pendidikan ini diharapkan dapat meningkatkan literasi, kesadaran, dan kompetensi keluarga Muslim serta generasi muda dalam mengelola keuangan sesuai syariah, sehingga tercapai kesejahteraan finansial yang selaras dengan keberlanjutan spiritual dan sosial. Dengan demikian, literasi keuangan syariah dapat menjadi instrumen strategis dalam memperkuat ketahanan ekonomi umat sekaligus meneguhkan nilai keislaman dalam kehidupan sehari-hari.